It Ends With Us - Hoover, Colleen (New York Simon & Schuster, 2016)
It Ends with Us is a young adult romance novel by Colleen Hoover, published by Atria Books on August 2, 2016. Based on the relationship between her mother and father, Hoover described it as "the hardest book I've ever written". It explores themes of domestic violence and emotional abuse.
Keywords: English- Novel